(untitled) (Journal of Patan Academy of Health Sciences, 2022)
Global surgery is interpreted differently and may lack an in-depth understanding which is complicated by socio-economy and culture. Global surgery and global health have become part of health care service following the report of the Lancet Commission. Sustainability, ethical principles, and decolonization are some important ongoing issues for recipient societies. Incorporating societal dimensions, socio-cultural values, patients’ needs, and affordability requires a tailored approach and not blindly pursuing the best technology. The recent COVID-19 has exposed the unethical and inequity in terms of equitable healthcare, vaccine rollout and its access, and unprecedented high mortality observed in some societies. Surgery has been a neglected stepchild of global health and in addition global surgery must not be a slave of technology for the promotion of the ‘gold standard’, especially corporate-led commercialized services because a sustainable and effective surgical service at a reduced cost is desirable for all, be resource-rich or poor. Global surgery and global health include health security and universal health coverage. Stakeholders of global surgery need to be aware that ‘one size does not fit all’ and are required to consider the diverse conditions.